IMPLEMENTATION OF SHARIA TOURISM ACCOMMODATION AT THE KRIYAD MURAYA HOTEL BANDA ACEH - Putra, Muhammad Rizki Mahalian; Sidiq, Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Hotels include business ventures that emphasize service sales. A sharia hotel is a hotel that implements a sharia system in a hotel which affects the way it is managed, the type of hotel, the hotel classification, to the sharia-compliant waste treatment. One of the activities carried out by sharia hotels is to attract customers in various ways without leaving the context of the sharia. Without this kind of implementation efforts to increase room sales are very difficult because many guests are still afraid to stay at Islamic hotels based on the principle of